The Anti-Inflammatory Effect of Human Telomerase-Derived Peptide on P. gingivalis Lipopolysaccharide-Induced Inflammatory Cytokine Production and Its Mechanism in Human Dental Pulp Cells. (28th October 2015) - Ko, Yoo-Jin; Kwon, Kil-Young; Kum, Kee-Yeon; Lee, Woo-Cheol; Baek, Seung-Ho; Kang, Mo K.; Shon, Won-Jun
Abstract : Porphyromonas gingivalis is considered with inducing pulpal inflammation and has lipopolysaccharide (LPS) as an inflammatory stimulator. GV1001 peptide has anticancer and anti-inflammation activity due to inhibiting activation of signaling molecules after penetration into the various types of cells. Therefore, this study examined inhibitory effect of GV1001 on dental pulp cells (hDPCs) stimulated by P. gingivalis LPS. The intracellular distribution of GV1001 was analyzed by confocal microscopy. Real-time RT-PCR was performed to determine the expression levels of TNF- α and IL-6 cytokines. The role of signaling by MAP kinases (ERK and p38) was explored using Western blot analysis. The effect of GV1001 peptide on hDPCs viability was measured by MTT assay. GV1001 was predominantly located in hDPC cytoplasm. The peptide inhibited P. gingivalis LPS-induced TNF- α and IL-6 production in hDPCs without significant cytotoxicity. Furthermore, GV1001 treatment markedly inhibited the phosphorylation of MAP kinases (ERK and p38) in LPS-stimulated hDPCs. GV1001 may prevent P. gingivalis LPS-induced inflammation of apical tissue. Also, these findings provide mechanistic insight into how GV1001 peptide causes anti-inflammatory actions in LPS-stimulated pulpitis without significantly affecting cell viability.